Impact of reperfusion therapy and infarct localization on frequency of premature ventricular beats in acute myocardial infarction - Davor Horvat; Josip Vincelj (Medicinski glasnik, 2015)
Aim: To determine the impact of infarct localization and types of reperfusion therapy on the frequency of ventricular premature beats (VPBs) in patients with acute myocardial infarction (AMI) and reduced left ventricular ejection fraction (LVEF). Methods: A total of 705 patients with acute ST elevation myocardial infarction (STEMI) were divided according to the infarct localization (anteroseptal, anterolateral, inferior and posterior) and reperfusion therapy (fibrinolysis or percutaneous coronary intervention with stenting) into two groups: LVEF<45% was an experimental group and LVEF>45% was a control group. The occurrence of VPBs<10 per hour was defined as a non-significant, and the occurrence of VPBs>10 per hour defined as a significant. Results: In patients with fibrinolysis therapy and LVEF<45% significant number of VPBs were in anteroseptal (p=0.017), anterolateral (p<0.001) and posterior AMI (p<0.001), but in patients with percutaneous coronary intervention (PCI) and LVEF<45% significant number of VPBs were only in anteroseptal AMI (p=0.001) localization. Conclusion: In patients with reduced ejection fraction in AMI, treatment with PCI method has a better antiarrhythmic effect compared to fibrinolysis treatment.
Keywords: fibrinolysis; percutaneous coronary intervention; ventricular arrhythmias